Laser altimeter data obtained over sea-ice during the SIZONet campaign in Apr, 2007 - Stefan Hendricks; Christian Haas; Thomas Krumpen (PANGAEA, 2024)
Sea ice surface roughness data were obtained during the SIZONet campaign in Apr, 2007 with a Single Beam Laser Altimeter (SBLA) mounted inside an electromagnetic system (EM-Bird) towed at 10-30 m height above surface by a Helicopter (Unknown model). A method developed by Hibler (1972) was used to a) isolate the surface profile from low-frequency variations associated with the aircraft motion and b) to identify pressure ridge sails. The processing steps are described in https://epic.awi.de/id/eprint/56364/. We applied a ridge detection threshold of 0.6 m, which means that only sails higher 0.6 m are detected. Version and name of the processing routine: Laser_Altimeter_Processing_VS5_06_20.py (vers.5, Feb 22, 2024, https://gitlab.awi.de/sitem/sbla_processing.git). SBLA records (RIEGL - LD90) are provided at a sampling rate of 100 Hz. Sensor accuracy is 5 cm with a beam diameter at surface of 5.8 cm. This dataset includes recorded altimeter readings, the derived surface elevation and width/height/spacing of detected pressure ridge sails. Note on data quality: 5.8 cm .